2023
DOI: 10.3390/antibiotics12081330
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Salmonella Species and Their Mobile Genetic Elements from Poultry Farm Environments in Malaysia

Syahidiah Syed Abu Thahir,
Sakshaleni Rajendiran,
Rafiza Shaharudin
et al.

Abstract: The prevalence and persistent outbreaks of multidrug-resistant (MDR) Salmonella in low-income countries have received growing attention among the public and scientific community. Notably, the excessive use of antibiotics in chicken feed for the purpose of treatment or as prophylaxis in the poultry industry have led to a rising rate of antimicrobial resistance. Therefore, this study aimed to determine the presence of antimicrobial-resistant Salmonella species and its mobile genetic elements from soil and efflue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Furthermore, in 2020, Wang and colleagues reported that 50% of the isolated Salmonella demonstrated multi-drug resistance in adult dairy cows [41]. In another study conducted in poultry farms in Malaysia, a high resistance level was reported against ampicillin and ciprofloxacin (62.5 and 45.8%); this could indicate its misuse in the agricultural sector [42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in 2020, Wang and colleagues reported that 50% of the isolated Salmonella demonstrated multi-drug resistance in adult dairy cows [41]. In another study conducted in poultry farms in Malaysia, a high resistance level was reported against ampicillin and ciprofloxacin (62.5 and 45.8%); this could indicate its misuse in the agricultural sector [42].…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella , a Gram-negative Enterobacteriaceae family member, stands as a predominant etiological agent of gastroenteritis [ 1 ]. Non-typhoidal Salmonella (NTS) , an extensive diversity within the Salmonella genus, which is evidenced by the documentation of more than 2600 serovars, is the most common enteric pathogen in animals and humans [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This poses a substantial and persistent threat to public health and is estimated to cause about 150 million illnesses and 60,000 deaths globally yearly [ 3 ]. These different NTS serovars are prevalent across diverse animal hosts, emphasizing the critical intersection between animal and human health [ 1 ].…”
Section: Introductionmentioning
confidence: 99%